The shellcoder's handbook : discovering and exploiting security holes - Koziol, Jack (Wiley Pub., 2004)
"Examines where security holes come from, how to discover them, how hackers exploit them and take control of systems on a daily basis, and most importantly, how to close these security holes so they never occur again."--Resource description page